Effects of Sesame (Sesamum indicum L.) Supplementation on Creatine Kinase, Lactate Dehydrogenase, Oxidative Stress Markers, and Aerobic Capacity in Semi-Professional Soccer Players - Barbosa, Carlos V. da Silva; Silva, Alexandre S.; de Oliveira, Caio V. C.; Massa, Nayara M. L.; de Sousa, Yasmim R. F.; da Costa, Whyara K. A.; Silva, Ayice C.; Delatorre, Plínio; Carvalho, Rhayane; Braga, Valdir de Andrade; Magnani, Marciane (Frontiers in Physiology, 2017)
Nutritional intervention with antioxidants rich foods has been considered a strategy to minimize the effects of overtraining in athletes. This experimental, randomized and placebo-controlled study evaluated the effects of consumption of sesame (Sesamum indicum L.) on muscle damage markers, oxidative stress, systemic inflammation and aerobic performance in male semi-professional soccer players. Twenty athletes were randomly assigned to groups that received 40 g (two tablespoons) per day of sesame or a placebo during 28 days of regular training (exposed to routine training that includes loads of heavy training in the final half of the season). Before and after intervention, creatine kinase (CK), lactate dehydrogenase (LDH), malondialdehyde (MDA), superoxide dismutase (SOD), C-reactive protein (hs-CRP) and aerobic capacity were evaluated. Before intervention, a physiologic imbalance was noted in both groups related to CK and LDH levels. Sesame intake caused a reduction of CK (19%, p<0.05), LDH (37%, p<0.05), MDA (55%, p <0.05) and hs-CRP (53%, p<0.05) and increased SOD (14%, p <0.05), vitamin A (25%, p <0.05) and vitamin E (65%, p<0.05) in the experimental group. These phenomena were accompanied by increased aerobic capacity (17%, p<0.05). The placebo group showed an increase in CK (5%, p<0.05) and no significant change in LDH, SOD or vitamin A. MDA levels decreased (21%, p<0.05) and vitamin E increased (14%, p<0.05) in the placebo group, but to a much lesser extent than in the experimental group. These results show that sesame consumption may reduce muscle damage and oxidative stress while improving the aerobic capacity in soccer players.